The Enterprise Risk Management , Investment Opportunity Set, and Corporate Social Responsibility on Firm Value: Evidence from Indonesian Consumer Non-Cyclicals - Putri Dian Ananda Harianja; Cahyaningsih (Academic Bright Collaboration, 2026)
Purpose - This study examines the effect of Enterprise Risk Management (ERM), Investment Opportunity Set (IOS), and Corporate Social Responsibility (CSR) on firm value among Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange during the 2022–2024 period, with Profitability (ROE) and Leverage (DAR) as control variables. The study is motivated by the empirical observation that this sector does not automatically ensure firm value stability, and by mixed findings in prior research on firm-value determinants in this sector. Methods - This quantitative study uses secondary panel data from 34 companies resulting 102 firm-year observations through purposive sampling. Firm value is proxied by Tobin's Q, ERM by the COSO ERM 2017 disclosure index (20 items), IOS by Market-to-Book Value of Equity, and CSR by the GRI Standards 2021 disclosure index (117 items). Data were analyzed using EViews 13 through the Random Effect Model selected through Chow, Hausman, and Lagrange Multiplier tests. Findings - ERM, IOS, CSR, ROE, and DAR simultaneously and significantly affect firm value. Partially, only IOS exerts a significant positive effect and DAR a significant negative effect, while ERM, CSR, and ROE do not reach statistical significance. These results indicate that firm value in this sector is more strongly driven by market-based growth signals than by disclosure-based signals, consistent with signalling theory. Research implications - The informational efficacy of corporate signals is contingent upon their nature and real-time market interpretability. ERM and CSR disclosures require substantially greater substantive depth and credibility to become value-relevant in capital markets, rather than serving as compliance-oriented reporting instruments. Originality - This study integrates ERM, IOS, and CSR simultaneously within a signalling theory framework that unifies two distinct categories of corporate signals: a market-based signal (IOS) and disclosure-based signals (ERM and CSR), demonstrating that market-based growth signals retain superior value relevance over disclosure-based signals in a stable sector context.